The Notch ligand Jagged2 promotes lung adenocarcinoma metastasis through a miR-200–dependent pathway in mice - Yang, Yanan (American Society for Clinical Investigation, 2011)
Epithelial tumor cells transit to a mesenchymal state in response to extracellular cues, in a process known as epithelial-to-mesenchymal transition (EMT). The precise nature of these cues has not been fully defined, an important issue given that EMT is an early event in tumor metastasis. Here, we have found that a population of metastasis-prone mouse lung adenocarcinoma cells expresses Notch and Notch ligands and that the Notch ligand Jagged2 promotes metastasis. Mechanistically, Jagged2 was found to promote metastasis by increasing the expression of GATA-binding (Gata) factors, which suppressed expression of the microRNA-200 (miR-200) family of microRNAs that target the transcriptional repressors that drive EMT and thereby induced EMT. Reciprocally, miR-200 inhibited expression of Gata3, which reversed EMT and abrogated metastasis, suggesting that Gata3 and miR-200 are mutually inhibitory and have opposing effects on EMT and metastasis. Consistent with this, high levels of Gata3 expression correlated with EMT in primary tumors from 2 cohorts of lung adenocarcinoma patients. These findings reveal what we believe to be a novel Jagged2/miR-200–dependent pathway that mediates lung adenocarcinoma EMT and metastasis in mice and may have implications for the treatment of human epithelial tumors.